Monotonic Tension-Torsion Experiments and FE Modeling on Notched Specimens Produced by SLM Technology from SS316L - Kořínek, Michal; Halama, Radim; Fojtík, František; Pagáč, Marek; Krček, Jiří; Krzikalla, David; Kocich, Radim; Kunčická, Lenka (Materials (Basel, Switzerland), 2020)
The aim of this work was to monitor the mechanical behavior of 316L stainless steel produced by 3D printing in the vertical direction. The material was tested in the "as printed" state. Digital Image Correlation measurements were used for 4 types of notched specimens. The behavior of these specimens under monotonic loading was investigated in two loading paths: tension and torsion. Based on the experimental data, two yield criteria were used in the finite element analyses. Von Mises criterion and Hill criterion were applied, together with the nonlinear isotropic hardening rule of Voce. Subsequently, the load-deformation responses of simulations and experiments were compared. Results of the Hill criterion show better correlation with experimental data. The numerical study shows that taking into account the difference in yield stress in the horizontal direction of printing plays a crucial role for modeling of notched geometries loaded in the vertical direction of printing. Ductility of 3D printed specimens in the "as printed" state is also compared with 3D printed machined specimens and specimens produced by conventional methods. "As printed" specimens have 2/3 lower ductility than specimens produced by a conventional production method. Machining of "as printed" specimens does not affect the yield stress, but a significant reduction of ductility was observed due to microcracks arising from the pores as a microscopic surface study showed.
Keywords: isotropic hardening; additive manufacturing; multiaxial loading; finite element method (FEM); plasticity; digital image correlation method; stainless steel 316L; hill yield criterion